2016
DOI: 10.1371/journal.pcbi.1005231
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization and Random Triggering of Lymphatic Vessel Contractions

Abstract: The lymphatic system is responsible for transporting interstitial fluid back to the bloodstream, but unlike the cardiovascular system, lacks a centralized pump-the heart–to drive flow. Instead, each collecting lymphatic vessel can individually contract and dilate producing unidirectional flow enforced by intraluminal check valves. Due to the large number and spatial distribution of such pumps, high-level coordination would be unwieldy. This leads to the question of how each segment of lymphatic vessel responds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 45 publications
3
28
0
Order By: Relevance
“…NIRF imaging showed that the lowest contraction frequency was measured after an injection of 20 μl of contrast agent ( Figure 2D). This is similar to what others have reported in ex vivo measurements of lymphatic vessels when a favorable pressure gradient was imposed, likely causing a shear-dependent response (18,20,(24)(25)(26). (Figure 2, A-D and Supplemental Videos 1-3; supplemental material available online with this article; https://doi.org/10.1172/jci.insight.96591DS1).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…NIRF imaging showed that the lowest contraction frequency was measured after an injection of 20 μl of contrast agent ( Figure 2D). This is similar to what others have reported in ex vivo measurements of lymphatic vessels when a favorable pressure gradient was imposed, likely causing a shear-dependent response (18,20,(24)(25)(26). (Figure 2, A-D and Supplemental Videos 1-3; supplemental material available online with this article; https://doi.org/10.1172/jci.insight.96591DS1).…”
Section: Resultssupporting
confidence: 88%
“…Lymphatic contraction reduction in the presence of increased flow suggests there is flow-mediated dilation and contraction inhibition due to the presence of a favorable upstream pressure gradient, which has been reported via ex vivo analysis of lymphatic vessels subjected to step-wise increasing pressures (18,20,(24)(25)(26). Similar results of increased lymph flow have been reported with intravital imaging of rats experiencing edemagenic stress (30).…”
Section: Discussionsupporting
confidence: 67%
“…Our previous work has elucidated how these behaviors are coordinated throughout the lymphatic system by mechano-sensitive feedback 15,16 . In summary, our model shows that and NO concentrations establish complementary and oscillatory feedback loops that are self-regulating, maintaining normal lymphatic function, in agreement with experimental observations 12,1719 .…”
Section: Introductionmentioning
confidence: 99%
“…The resulting model was able to control lymphatic transport via mechanobiological feedback loops, given by stretch-activated contractions and flow-induced relaxations. Very recently, Baish et al [83] proposed a model of a vascular oscillator and studied the interaction of Ca 2+ and NO in the context of lymphatic vessel contractions.…”
mentioning
confidence: 99%
“…With the aim of constructing a mathematical model of the entire lymphatic system, the above-mentioned mathematical models for lymphangions, except for [14,83], are based on a relatively simple contraction dynamic. As a matter of fact, these models 1) prescribe muscle contractility dynamics by using trigonometric functions, and 2) artificially prescribe time delays between adjacent lymphangions.…”
mentioning
confidence: 99%